2012
DOI: 10.1016/j.neuroscience.2012.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Strong neuroprotection with a novel platinum nanoparticle against ischemic stroke- and tissue plasminogen activator-related brain damages in mice

Abstract: Reactive oxygen species (ROS) are major exacerbation factor in acute ischemic stroke, and thrombolytic agent tissue plasminogen activator (tPA) may worsen motor function and cerebral infarcts. The platinum nanoparticle (nPt) is a novel ROS scavenger, and thus we examined the clinical and neuroprotective effects of nPt in ischemic mouse brains. Mice were subjected to transient middle cerebral artery occlusion (tMCAO) for 60 min and divided into the following four groups by intravenous administration upon reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 55 publications
2
65
0
Order By: Relevance
“…We have previously shown that delivery of SOD-loaded NPs via carotid artery at the time of reperfusion in an MCAO model in rats was significantly more effective in preventing reperfusion injury than SOD in solution or untreated control; treatment with antioxidant NPs mitigated the ROS levels, reduced BBB leakage, and protected neuronal cells from apoptosis, leading to steady neurological recovery with concomitant reduction in infarct volume over 4 weeks [17]. Others have also demonstrated similar efficacy in the MCAO model with antioxidant-loaded NPs [38] and other formulations of NPs that mitigated the ROS levels in the ischemic brain [39]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that delivery of SOD-loaded NPs via carotid artery at the time of reperfusion in an MCAO model in rats was significantly more effective in preventing reperfusion injury than SOD in solution or untreated control; treatment with antioxidant NPs mitigated the ROS levels, reduced BBB leakage, and protected neuronal cells from apoptosis, leading to steady neurological recovery with concomitant reduction in infarct volume over 4 weeks [17]. Others have also demonstrated similar efficacy in the MCAO model with antioxidant-loaded NPs [38] and other formulations of NPs that mitigated the ROS levels in the ischemic brain [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rtPA treatment initiated after the therapeutic window may even worsen ischemic brain injury. rtPA-induced brain damage has been found to be associated with increased ROS (Takamiya et al, 2012), so coadministration of rtPA with agents that dampen ROS production might afford robust cerebroprotection. However, conventional antioxidants have been found generally ineffective at protecting ischemic brain or preserving neurocognitive function in stroke victims (Sutherland et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…173 Similarly, platinum nanoparticles showed their antioxidant property which reported lowering cerebral cortex volume and improved motor function in stroke animal model. 174 Irreversible caspase-3 inhibitor loaded transferrin targeted nanospheres provide a reduction in infarct volume in ischemic brain. 175 SiRNA loaded carbon nanotube also documented as potential therapeutics in stroke treatment.…”
Section: Strokementioning
confidence: 99%